KSHV Induction of Angiogenic and Lymphangiogenic Phenotypes - DiMiao, Terri A.; Lagunoff, Michael (Frontiers in Microbiology, 2012)
Kaposi’s Sarcoma is a highly vascularized tumor supporting large amounts of neo-angiogenesis. The major cell type in KS tumors is the spindle cell, a cell that expresses markers of lymphatic endothelium. KSHV, the etiologic agent of KS, is found in the spindle cells of all KS tumors. Considering the extreme extent of angiogenesis in KS tumors at all stages it has been proposed that KSHV directly induces angiogenesis in a paracrine fashion. In accordance with this theory, KSHV infection of endothelial cells in culture induces a number of host pathways involved in activation of angiogenesis and a number of KSHV genes themselves can induce pathways involved in angiogenesis. Because spindle cells are phenotypically endothelial in nature, activation through the induction of angiogenic and/or lymphangiogenic phenotypes by the virus may also be directly involved in spindle cell growth and tumor induction. Accordingly, KSHV infection of endothelial cells induces cell autonomous angiogenic phenotypes to activate host cells. KSHV infection can also reprogram blood endothelial cells to lymphatic endothelium. However, KSHV induces some blood endothelial specific genes upon infection of lymphatic endothelial cells creating a phenotypic intermediate between blood and lymphatic endothelium. Induction of pathways involved in angiogenesis and lymphangiogenesis are likely to be critical for tumor cell growth and spread. Thus, induction of both cell autonomous and non-autonomous changes in angiogenic and lymphangiogenic pathways by KSHV likely plays a key role in the formation of KS tumors.